Function and Benefits Digital Technology in Increase Performance at Bank Jabar Banten Branch Office Sharia Servant Subang - Ismailiyya, Nathisa; Khalid, Nour; Purnamasari , Yesa (Ecobankers : Journal of Economy and Banking, 2025)
This article is motivated because it is not yet fully known whether digital technology has an important role and benefits in improving the performance of Bank BJB Syariah KCP Subang. This article aims to Analyze the Function and benefits of digital technology in improving performance at BJB Syariah Bank KCP Subang, Digital technology is one that is very much needed in business development, especially in the banking world because almost the majority use technology to facilitate their performance and business, even digital technology is called the most important element for the development of the business world today. The method in this study uses a qualitative method. This qualitative research is used to understand and explain social phenomena in depth by emphasizing meaning and context, which is supported by references from literature relevant to digital technology. This research was carried out at the BJB sharia bank KCP Subang. The data sources obtained in this study come from primary data sources taken from the results of interviews related to Digital Technology while secondary data sources are taken from literature studies in the form of publications and written narratives related to the benefits of digital technology in improving performance at BJB Syariah Bank KCP Subang. The type of data used is qualitative data with data collection techniques through interviews and supported by literature searches related to the Function and benefits of digital technology. Data Analysis Techniques use descriptive analysis to describe the results of the research that has been studied. Based on the results of this study, it shows that the Function and Benefits of Technology at BJB Syariah Bank KCP Subang can facilitate work and improve performance. This research makes a significant contribution by revealing the concrete role of digital technology in improving the performance of Bank BJB Syariah KCP Subang. The recommendation of the results of this study is for banks to improve the quality and stability of digital technology systems, especially the Mobile Maslahah application, by conducting regular updates and increasing server capacity to overcome unstable network constraints.